Salaam Greeting to Spread Peace in The Archipelago of Indonesia - Nesia Andriana (LPPM IAIN Kudus, 2018)
Maintaining peace in the world has always been a noble aim, yet it remains an endless polemic. The archipelago of Indonesia, known as Nusantara, is home to more than 600 ethnic groups and if it is not well organized, it can lead to conflicts. This study aims to examine Islamic values, especially those conveyed in the hadeeths of Saheeh Bukhari, the Chapter on Seeking Permission. The focus of this study is to examine the relevant hadeeths to identify the pillars that Muslims can use to build and nurture peace in the archipelago. This research is conducted through literature review approach. The content of the hadeeths is associated with events that occurred in Nusantara, both in the era of independence and in the era of reform to reveal the potentials of Muslims as a majority, to maintain peace and unity throughout the archipelago. The study reveals that the saheeh hadeeths related to greeting of salaam and its rules contain the basic pillars that can contribute to sustaining peace in the archipelago. These pillars ensure the security and safety of individuals’ privacy, public comfort, prevention of riots and conflicts, news monitoring, and maintain humanitarian values to always promote peace in stead of hostility. These values are still embraced in general by Muslims in the archipelago. The Muslims still observe the principles of Bhineka Tunggal Ika and Pancasila, which are key to maintain peace and unity of the homeland.